Metaphysics what there is - Kononovich, Lila; Garcia, Pablo; Films for the Humanities & Sciences (New Jersey : Films for the Humanities & Sciences, 2004)
In this program, Rutgers philosophers Brian McLaughlin, Barry Loewer, John Hawthorne, Ted Sider, and Dean Zimmerman discuss the nature of this most ancient branch of philosophy, exploring concepts of causation, time, necessity, and possibility and contemplating the big questions of 2Who am I?3 and 2Where am I?3 In the process, they reference the works and theories of Aristotle, Plato, William of Ockham, Hume, Kant, Mill, Leibniz, and others
Title from title screen
Executive producers, Chris Scherer, Camila O'Donnell
DVD format
Keywords: Philosophy; Metaphysics; Philosophy -- istory